1993
DOI: 10.1289/ehp.93101s383
|View full text |Cite
|
Sign up to set email alerts
|

Variability in chromosome aberrations, sister chromatid exchanges, and mitogen-induced blastogenesis in peripheral lymphocytes from control individuals.

Abstract: Confidence in results from monitoring genetic end points in environmentally or occupationally exposed individuals can be improved with knowledge of the normal variability of changes in genetic end points in the general population. Confounding effects can be determined, and study interpretation can be improved by correlation of this variability with various lifestyle factors such as sex and age, smoking and drinking habits, viral infections, exposure to diagnostic X-rays, etc. Eight blood samples were taken fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 25 publications
2
0
0
Order By: Relevance
“…It could be explained by the fact that during chronic exposure part of the chromosomal aberrations can be eliminated in vivo by the death of lymphocytes. Similarly, according to published data , results of our study indicated that the age did not seem to influence the levels CAs and SCEs in both exposed and control subjects (Table ).…”
Section: Discussionsupporting
confidence: 89%
“…It could be explained by the fact that during chronic exposure part of the chromosomal aberrations can be eliminated in vivo by the death of lymphocytes. Similarly, according to published data , results of our study indicated that the age did not seem to influence the levels CAs and SCEs in both exposed and control subjects (Table ).…”
Section: Discussionsupporting
confidence: 89%
“…A seasonal influence on genotoxic biomarkers in a Polish population has been already observed by Perera et al (20) and by Anderson et al (15,21) in a United Kingdom control population. Our data also confirm that there is some seasonal effect on cytogenetic damage, both in the whole population and in the unexposed subgroup where responses are higher in winter.…”
Section: Discussionsupporting
confidence: 53%